2022
DOI: 10.26633/rpsp.2022.73
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of the prevalence of selected sexually transmitted infections in young people in Latin America

Abstract: Objective. To estimate the burden of Chlamydia trachomatis (CT), Neisseria gonorrhoeae (NG), Treponema pallidum (TP), and human papillomavirus (HPV) infections among people aged 10 to 25 in Latin America and the Caribbean. Methods. The MEDLINE, EMBASE, and LILACS databases were searched, as well as documents from regional organizations or national health Institutions. Population-based studies that reported prevalence or incidence of CT, NG, TP, and HPV detected through confirmatory tests in adolescents and y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 38 publications
0
4
0
3
Order By: Relevance
“…2023; 3:257 2 reproductiva (SSR) entre los adolescentes. En un estudio realizado en América Latina (13) en una población de edades entre los 10 y 25 años, mostró al virus del papiloma humano y la clamidia como enfermedades con una mayor prevalencia frente a las otras ETS como es el caso de la gonorrea y sífilis. Las infecciones de transmisión sexual en mujeres constituyen un gran problema de salud pública, donde la mayor incidencia es el dolor pélvico, seguido de la secreción vaginal, el condiloma, VIH/SIDA, sífilis, herpes genital y la blenorragia, teniendo una manera ascendente dentro del estudio especialmente el VIH/SIDA.…”
Section: Resultsunclassified
See 1 more Smart Citation
“…2023; 3:257 2 reproductiva (SSR) entre los adolescentes. En un estudio realizado en América Latina (13) en una población de edades entre los 10 y 25 años, mostró al virus del papiloma humano y la clamidia como enfermedades con una mayor prevalencia frente a las otras ETS como es el caso de la gonorrea y sífilis. Las infecciones de transmisión sexual en mujeres constituyen un gran problema de salud pública, donde la mayor incidencia es el dolor pélvico, seguido de la secreción vaginal, el condiloma, VIH/SIDA, sífilis, herpes genital y la blenorragia, teniendo una manera ascendente dentro del estudio especialmente el VIH/SIDA.…”
Section: Resultsunclassified
“…representan un desafío para la salud sexual y reproductiva y que pueden impactar en los niveles de embarazos precoces, matrimonios juveniles e infecciones para los centros asistenciales, para lo que se deben considerar los factores económicos, culturales, sociales, políticos y financieros que incluyan en la integración de la educación en los sistemas nacionales. Por otra parte, Vallejo et al (13) , en su estudio, en el que se enfocaron en determinar las posibles causas para la prevalencia y el aumento de las enfermedades de transmisión sexual, destacando las creencias populares como factor predominante para el acceso a la información, siendo la prevalencia de infecciones por CT, NG, TP o VPH en poblaciones de 10 a 25 años, donde se encontró que la prevalencia de la infección por CT varió del 2,1 % al 30,1 %, la NG del 0 % al 2,9 %, la sífilis del 0 % al 0,7 % y el VPH del 25,1 % al 55,6 %. De igual forma, un estudio realizado en Uruguay, (14) mostró que los adolescentes manifestaron que los conocimientos sobre la salud sexual y reproductiva se obtienen principalmente de los padres en un 35 %, amigos 20 %, médicos 8 % y otros en un 18 %, arrastrando factores culturales y otros considerados tabú como base de los conocimientos que aplicaran en el desarrollo y cuidado de su vida sexual.…”
Section: Discussionunclassified
“…Two reviews involving populations of female sex workers, one in China (2000–2011) and one in Africa (1999–2019), reported a gonorrhoea prevalence of 6% and 5.46% respectively [ 149 , 150 ], similar to our results in the high-risk population. A systematic review of the prevalence of four STDs in young people aged 10–25 years in LAC was published in 2022, after the cut-off date for our search [ 151 ]. This review identified 15 population-based studies, of which eight reported data on the prevalence of N. gonorrhoeae .…”
Section: Discussionmentioning
confidence: 99%
“…This review identified 15 population-based studies, of which eight reported data on the prevalence of N. gonorrhoeae . Prevalence in women ranged from 0 to 2.9% (8 studies, 4845 participants), prevalence in pregnant women was 1% (1 study, 2071 participants), and prevalence in men aged < 20 years was 0% (2 studies, 666 participants) [ 151 ]. The results from this review are specific to populations aged 10–25 years [ 151 ] and therefore cannot be compared directly with the results from our study which included subjects of all ages.…”
Section: Discussionmentioning
confidence: 99%
“…A challenge for the region is the impact of unequal social and economic development across countries ( Gavin et al , 1998 ; Amarante et al , 2016 ). Also, challenging male attitudes are still present, characterized by an hegemonic masculinity in male sexual and reproductive attitudes and relationships ( Díaz-Rojas et al , 2020 ) that may translate to low vasectomy rates ( Sanchez-Molano et al , 2019 ) and to a perception of no risk of STIs, highlighting the need for public health policies for prevention, early diagnosis, and treatment of STIs in young people ( Vallejo-Ortega et al , 2022 ). Additionally, there is a lack of andrology registries and regional EQA programs, and professional development relies on personal self-improvement.…”
Section: Mrh: a Global Perspectivementioning
confidence: 99%